Quantification of arthropod species resources using distance-based measures – Ground beetles as focal group. (March 2023) - Hansen, Rikke Reisner; Damgaard, Christian Frølund; Kjær, Christian; Rasksen, Mads Blikdorff; Thomsen, Philip Francis; Strandberg, Morten Tune
Highlights: Measurement and data treatment of multiple species ground beetle responses to measured resources was possible and meaningful. Operationalizing the resource habitat concept can benefit integration of arthropods in monitoring. Distance based measures of important ground beetle resources reliably predict variation in ground beetle assemblages. Generalist predator guilds, such as ground beetles, respond to resource abundance measures. Abstract: Operational methods for reliably quantifying habitat association of arthropod species are highly warranted in species conservation. A distance-based abundance measure called Integral Occurrence Probability (IOP) offers the possibility of quantifying the abundance of specific resources, essential for lifecycle completion in arthropods. We propose and test a new method integrating the measure of Relative Annulus Area (RAA), which is the fundamental measurement when calculating IOP, as a way of operationalizing habitat assessments and thus, better integrating arthropod habitats in species monitoring. We used abundance data for ground beetles (Carabidae) collected at 100 plots in a Danish coastal heathland and registered the RAA for important ground beetle resources. Using a model-based ordination technique that allows for the integration of species traits to aid in the analysis of species-environment association, we identified six important heathland structures significantly associated with the distribution of ground beetle species assemblages. The structures along with the overall directionality of the association (parentages) were bare sandy patches (+), water (−), dwarf shrubs (+), vegetation patches above 25 cm. (+), and refuges (+). These variables explained from 0.20 ( Pterostichus. melanarius ) to 0.99 ( Carabus problematicus ) and for the model including abundance weighted trait values, r 2 ranged from 0.42 ( Pterostichus niger ) to 0.93 ( Carabus melanocephalus ). Distance based measures of important ecological resources for arthropods may be used as an addition to current national monitoring programs, and thus enabling implementation of specific life cycle needs of endangered arthropod groups.